Solitary atrial metastases: a rare clinical challenge. (30th March 2011) - Eminowicz, Gemma; Achilleos, Katerina; Payne, Simon; Davies, John; Robinson, Anne
Abstract : This case describes a 55-year-old lady presenting with lethargy, migraines and a cardiac mass on a background history of breast cancer. She had been treated initially with a mastectomy, axillary node clearance, reconstruction and hormone manipulation followed by chemotherapy and high dose radiotherapy for an isolated supraclavicular metastases. She was disease free for 5 years when she complained of lethargy and migraines. A CT confirmed an isolated cardiac lesion, confirmed on echocardiogram A percutaneous atrial biopsy revealed an atrial metastases from breast carcinoma. She was treated with chemotherapy achieving a good response but was still deemed inoperable after treatment. She currently is receiving letrozole.